2012
DOI: 10.1186/1479-5876-10-221
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure pulsed focused ultrasound with microbubbles promotes an anticancer immunological response

Abstract: BackgroundHigh-intensity focused-ultrasound (HIFU) has been successfully employed for thermal ablation of tumors in clinical settings. Continuous- or pulsed-mode HIFU may also induce a host antitumor immune response, mainly through expansion of antigen-presenting cells in response to increased cellular debris and through increased macrophage activation/infiltration. Here we demonstrated that another form of focused ultrasound delivery, using low-pressure, pulsed-mode exposure in the presence of microbubbles (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 53 publications
1
70
0
1
Order By: Relevance
“…Among non-thermal effects, the transfer of mechanical energy seems to be able to induce cascade phenomena that could profoundly affect the host response. A most intriguing phenomenon is the modulation of immune-response: the disintegration of neoplastic masses induced by vibration seems to enhance the anti-tumor immune-surveillance by amplification of cancer antigens (81,82). Zhou et al demonstrated a significant decrease of immunosuppressive cytokines after HIFU, which means a shift towards improved anti-cancer immune response (23).…”
Section: Discussionmentioning
confidence: 99%
“…Among non-thermal effects, the transfer of mechanical energy seems to be able to induce cascade phenomena that could profoundly affect the host response. A most intriguing phenomenon is the modulation of immune-response: the disintegration of neoplastic masses induced by vibration seems to enhance the anti-tumor immune-surveillance by amplification of cancer antigens (81,82). Zhou et al demonstrated a significant decrease of immunosuppressive cytokines after HIFU, which means a shift towards improved anti-cancer immune response (23).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ablation 246,258,263 and sparse-scan ablation protocols 254 that do not fully denature tumor antigens improve antigen presenting cell (APC) activation compared to thermal protocols, indicating that non-thermal approaches may be more effective in generating an antigen-specific systemic antitumor response. Furthermore, low intensity pulsed ultrasound with microbubbles (US) has been shown to enhance delivery of NK cells to tumors 266 , increase T cell infiltration in response to ultrasound-induced tumor ischemia 268 , and increase the CD8/Treg ratio while providing modest tumor growth control 267 . Our results with US, demonstrating improved tumor growth control, increased CD4, CD8, and NK populations, and increased CD8/Treg ratios, agree nicely with this body of work and further support the hypothesis that US should synergize with PD-1 therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The CD8/Treg ratio was significantly improved by day 3 and remained elevated at day 18. 267 Given the pressures used and the marked enhancement in dextran permeability, it is certain that this protocol produced vascular disruption within the tumor. Hunt et al utilized low-power US in combination with microbubbles in a protocol designed to decreased tumor perfusion, under the assumption that antivascular therapy can induce a hypoxia-mediated immune response.…”
Section: Ultrasound As An Immune Adjuvantmentioning
confidence: 99%
See 2 more Smart Citations